PELATIHAN VOKAL TEMBANG SUNDA SEBAGAI MEDIA PEMBINAAN KARAKTER WARGA BINAAN LAPAS KELAS III RANGKASBITUNG - Palguna Edya Wibisana; Dadang Dwi Septiyan; Alis Triena Permanasari; Adi Maulana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Correctional institutions are no longer viewed merely as places of detention but have evolved into spaces for the personal transformation of inmates. This article examines the effectiveness of Tembang Sunda vocal training as a character development instrument at Class III Correctional Institution Rangkasbitung. The study employs a qualitative descriptive-analytical approach, with data collected through participatory observation, in-depth interviews, and documentation during the training process. Two repertoires were strategically selected—Sapu Nyere Pegat Simpay and Alam Banten Anu Urang—both carrying philosophical content on unity, social responsibility, and attachment to local identity. Findings indicate that contemplative and repetitive vocal activities facilitate psychological catharsis while organically instilling character values. Moral internalization through lyrical reflection stimulates self-examination among inmates and encourages behavioral reorientation toward more constructive patterns. These findings affirm that traditional local wisdom arts can serve as a relevant and sustainable humanistic rehabilitation approach within correctional environments.